Analysis of the process parameters affecting the bone burring process: An in‐vitro porcine study. Issue 5 (23rd August 2019) - Kusins, Jonathan R.; Tutunea‐Fatan, O. Remus; Athwal, George S.; Ferreira, Louis M.
Abstract: Background: A stable bone burring process, which avoids thermal osteonecrosis and minimizes harmful vibrations, is important for certain orthopedic surgical procedures, and especially relevant to robot‐operated bone burring systems. Methods: An experimental characterization of the effects of several bone burring process parameters was performed. Burring parameters were evaluated by resultant bone temperature, tool vibration, and burring force. Results: An optimal combination of bone burring parameters produced minimums in both bone temperature (<40°C) and tool vibration (<4 g‐rms). A cylindrical burr, oriented normal to the specimen, resulted in significantly higher temperatures (50.8 ± 6.8°C) compared with a spherical burr (33.5 ± 4.3°C) ( P = .008). Regardless of the parameters tested, burring forces were less than 10 N. Conclusions: The recommended configuration, which minimized both bone temperature and vibrations experimentally, was a 6‐mm spherical burr at 15 000 rpm with a 2 mm/s feed rate.